Construção do binómio: interculturalidade e as pessoas surdas - Martínez Atanacio, Mariana (2024)
This paper focused on the review of documentary sources on interculturality and Deaf people in Latin America. The objectivewas to identify the relationship and the contribution of such perspective in the studies, through the search and compilation of materials published in four open access databases. For this purpose, the qualitative approach and documentary research were used. It involved the systematic review, elaboration of content cards, classification, cross-checking of information and organization of the following categories: approach, bilingual, knowledge and education. The major challenge was the theoretical and empirical reflection of the documents to determine the binomial link. The results showed the presence of symmetry in the educational proposal aimed at indigenous peoples with deaf communities by the conception of linguistic minorities.